40-year trends in an index of survival for all cancers combined and survival adjusted for age and sex for each cancer in England and Wales, 1971–2011: a population-based study - Quaresma, Manuela; Coleman, Michel P; Rachet, Bernard (The Lancet (British edition), 2015)
Assessment of progress in cancer control at the population level is increasingly important. Population-based survival trends provide a key insight into the overall effectiveness of the health system, alongside trends in incidence and mortality. For this purpose, we aimed to provide a unique measure of cancer survival. In this observational study, we analysed trends in survival with population-based data for 7·2 million adults diagnosed with a first, primary, invasive malignancy in England and Wales during 1971–2011 and followed up to the end of 2012. We constructed a survival index for all cancers combined using data from the National Cancer Registry and the Welsh Cancer Intelligence and Surveillance Unit. The index is designed to be independent of changes in the age distribution of patients with cancer and of changes in the proportion of lethal cancers in each sex. We analysed trends in the cancer survival index at 1, 5, and 10 years after diagnosis for the selected periods 1971–72, 1980–81, 1990–91, 2000–01, 2005–06, and 2010–11. We also estimated trends in age-sex-adjusted survival for each cancer. We define the difference in net survival between the oldest (75–99 years) and youngest (15–44 years) patients as the age gap in survival. We evaluated the absolute change (%) in the age gap since 1971. The overall index of net survival increased substantially during the 40-year period 1971–2011, both in England and in Wales. For patients diagnosed in 1971–72, the index of net survival was 50% at 1 year after diagnosis. 40 years later, the same value of 50% was predicted at 10 years after diagnosis. The average 10% survival advantage for women persisted throughout this period. Predicted 10-year net survival adjusted for age and sex for patients diagnosed between 2010 and 2011 ranged from 1·1% for pancreatic cancer to 98·2% for testicular cancer. Net survival for the oldest patients (75–99 years) was persistently lower than for the youngest (15–44 years), even after adjustment for the much higher mortality from causes other than cancer in elderly people. These findings support substantial increases in both short-term and long-term net survival from all cancers combined in both England and Wales. The net survival index provides a convenient, single number that summarises the overall patterns of cancer survival in any one population, in each calendar period, for young and old men and women and for a wide range of cancers with very disparate survival. The persistent sex difference is partly due to a more favourable cancer distribution in women than men. The very wide differences in survival for different cancers, and the persistent age gap in survival, suggest the need for renewed efforts to improve cancer outcomes. Future monitoring of the cancer survival index will not be possible unless the current crisis of public concern about sharing of individual data for public health research can be resolved. Cancer Research UK.